Spiritual reminiscence therapy– is it effective for older people? - Syed Elias, Sharifah Munirah; Neville, Christine; Scott, Theresa (2016)
Introduction: Reminiscence therapy (RT) provides various benefits to older people but numerous studies on the effectiveness of RT have yielded inconclusive results. The integration of a spiritual element in RT which is known as spiritual reminiscence therapy (SRT) may increase the effectiveness of RT. Spirituality is essential in later life as it buffers against depression and reduces the risks of developing loneliness, anxiety and depression. A SRT involves recall of past significant memories by emphasizing the meaning of memories and it guides older people to find meaning of life, future hopes and eventually improves the quality of life. Therefore, this paper aims to determine the effectiveness of a SRT program for older people with loneliness, anxiety and depression.